Inducing Drought Stress Tolerance during Germination by Micronutrient Seed Priming and Coating of Maize (Zea mays L.) - Ikasari, Yulfa Astuti; Suhartanto, M. Rahmad; Ilyas, Satriyas (Department of Agronomy and Horticulture, IPB University, 2025)
Drought is a significant abiotic stress that affects the germination of many crops, including maize. Improvement in seed quality and tolerance to drought stress can be induced through seed priming and coating. This research aimed to study the effect of priming and coating on maize seed germination under drought conditions. The experiment was performed in a randomized complete block design with a split plot arrangement and four replications. The main plot was drought stress level: control, and 10% PEG. The subplot was seed enhancement treatments, which consisted of untreated, hydropriming, osmopriming, priming with 6 mM Si, 0.075 mM Se + 10 mM Zn, 6 mM Si + 0.075 Se + 10 mM Zn, 0.8 mM melatonin, seed coating 1% NaAlg, P9: seed coating + 0.732 g Si.kg-1 seed, P10: seed coating + 0.014 g Se + 2.875 g Zn.kg-1 seed, P11: seed coating + 0.732 g Si + 0.014 g Se + 2.875 g Zn.kg-1 seed, and P12: seed coating + 0.186 g melatonin.kg-1 seed. The result showed that seed priming 0.075 mM Se + 10 mM Zn, priming 6 mM Si + 0.075 mM Se + 10 mM Zn, and seed coating + 0.732 g Si + 0.014 g Se + 2.875 g Zn.kg-1 seed improved maize seed germination under drought stress based on germination percentage, speed of germination, root dry weight, seedling dry weight, and seedling growth rate. Seed priming or coating with micronutrients such as silicon, selenium, and zinc could serve as an effective treatment to enhance germination of maize under drought conditions.